Pre-service teachers’ beliefs about English Language Teaching and Learning in EFL classroom: A review of literature - Pusparini, Ririn; Widiati, Utami; Susanti, Arik (Universitas Muhammadiyah Sidoarjo, 2021)
Pre-service teachers’ (PST) beliefs and practices have been agreed as an initially vital basis to continue maintaining a qualified learning process. This article reviews the research on PSTs’ beliefs and practices concerning teaching and learning English as a foreign language (EFL) and the exploration of the complex relationship between EFL PSTs’ beliefs and practices. It encompasses a discussion about the nature of teachers’ beliefs, an overview of PSTs’ belief formation, and some previous studies on PSTs’ beliefs. The review of related literature summarizes the empirical studies on PSTs’ beliefs and practices from 2011 up to 2020, which reveal the diversity and similarity of the studies on EFL PSTs’ beliefs. The result obtained in this study depicts that PSTs’ beliefs about EFL teaching and learning are affected by prior language learning experiences, teacher education, and teaching practices. Besides, some constraints in the classroom setting can trigger the beliefs change covering time restriction, curriculum emphasis, students’ misbehavior, students’ competence, students’ motivation, or even PSTs’ motivation and confidence. Finally, when their tacit beliefs turn into explicit beliefs, PSTs can identify and assess their beliefs attributed to their classroom practices, from which EFL PST education can be informed to design better courses and prepare PSTs’ future careers. HIGHLIGHTS: EFL PSTs’ beliefs are acquired from many years of learning experiences they got from schools to teacher education, of which the condition has influenced what and how they learn to teach. Their beliefs, then, influence what they say and do in the classroom, which, in turn, shapes their beliefs. Some constraints in the classroom setting can trigger the beliefs changed: time restriction, curriculum emphasis, students’ misbehavior, students’ competence, students’ motivation, or even PSTs’ motivation and confidence.